Interventions for reducing sedentary behaviour in people with stroke - Saunders, David H (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine whether interventions primarily intended to reduce time spent in sedentary behaviour after stroke reduce sedentary time, and whether they modify cardiovascular risk, and reduce the risk of death or secondary vascular events. We will also include interventions intended to reduce the length of prolonged uninterrupted periods of sedentary behaviour (i.e. interventions to fragment or interrupt). Primary objectives To determine whether interventions to reduce or interrupt sedentary time influence: mortality; recurrent cerebrovascular or cardiovascular events. Secondary objectives To determine whether interventions to reduce or interrupt sedentary time influence: amount of sedentary time; cardiometabolic risk profile (e.g. glucose tolerance, arterial function, blood cholesterol and blood pressure); adverse events (in addition to recurrent events, for example falls). Other objectives In addition, we will as a scoping exercise, describe the range of all outcome measures reported in all trials. By definition, any included study interventions will fall within the umbrella of physical activity.Therefore, it may be that multiple plausible benefits could emerge that are common to other energy‐expending interventions.